Does innovation affect credit access? New empirical evidence from Italian small business lending - Andrea Bellucci; Ilario Favaretto; Germana Giombini (Institut für Angewandte Wirtschaftsforschung (IAW), 2014)
In this paper we analyze the access to credit of innovative firms on the price and non-price dimensions of bank lending. Using information from two datasets, we use a propensity score matching procedure to estimate the impact of the innovative nature of firms on: (a) loan interest rates; (b) the probability of having to post collateral; and (c) the probability of overdrawing. Our analysis reveals that banks trade off higher interest rates and lower collateral requirements for firms involved in innovative processes. Further, innovative firms have a lower probability of being credit rationed than their non-innovative peers.
Keywords: D82; E43; D40; G21; 330; innovative firms; interest rate; firm's financing; relationship lending